Principal Component Analysis in Bitter Gourd (Momordica Charantia L.) (Bangladesh Journal of Botany, 2022)
Investigation was carried out to assess genetic diversity through principal component analysis (PCA) and D2 analysis. Twenty four genotypes of bitter gourd were grown in RBD with three replications including two checks (Pant karela-1 and Pant karela-2). Principal component analysis showed that the first Eigen root had maximum of 26.83% variation of total variation, while the first six principal component axes together with explained 84.05% variation, which were used for cluster analysis, suggesting first six principal axes are adequate to explain the variation in reduced dimension. Clustering through D2 analysis revealed maximum inter-cluster distance of 498.80 between clusters IV and V followed by cluster III and V (322.81). Thus the genotypes grouped under cluster V, IV and III may yield maximum heterosis upon hybridization and also create wide variability including transgressive segregants in selfed generations.Bangladesh J. Bot. 51(1): 1-7, 2022 (March)